Effects of TRX Suspension Training on Muscle Activity Onset and Its Potential Role in Anterior Cruciate Ligament Injury Prevention Among Female Athletes With Trunk Dominance Impairment - Narges Ziaee; Reza Rajabi; Yousef Moghadas Tabrizi; Hooman Minoonejad; Mohammad Karimizadeh Ardakani (Physical Treatments, 2025)
Purpose: Trunk dominance impairment (TDI) is a major risk factor for anterior cruciate ligament (ACL) injury in females. The purpose of this study was to investigate the effect of six weeks of total body resistance exercise (TRX) suspension training on muscle activity onset in selected lumbo-pelvic-hip muscles in female athletes with TDI. Methods: A semi-experimental design was employed to investigate the effects of TRX suspension training on muscle activity onset in 30 female athletes. Participants were recruited using purposive and convenience sampling. The tuck jump test identified athletes with TDI. Surface electromyography (EMG) recorded muscle activity onset of the transverse abdominis, external oblique, quadratus lumborum, gluteus maximus, and gluteus medius during a single-leg jump-landing task. Following pre-testing, the training group engaged in a six-week TRX suspension training program, consisting of three 30-45 minute sessions per week. A mixed-design ANOVA analyzed the data. Results: The results of the mixed-design ANOVA revealed that in the post-test phase, muscle activity onset improved only in the training group (P<0.05), while there was no significant difference in muscle activity onset between pre-test and post-test phases in the control group (P>0.05). Conclusion: TRX suspension training, due to its unstable nature, requires timely and anticipatory muscle activation. Therefore, it can be claimed that this training method has the potential to improve the muscle activity onset of lumbo-pelvic-hip muscles in female athletes with TDI. Hence, TRX suspension training used in this study is recommended to prevent ACL injury in female athletes with TDI.